Programming in concurrent logic languages - Huntbach, M.M.; Ringwood, G.A. (IEEE software, 1995)
The authors survey concurrent logic languages, which expand Prolog by dropping its built-in sequential search order. These languages make parallelism easy by avoiding the low-level constructs that result from a too direct translation of machine hardware into programmer's language.< >